A Randomized Controlled Evaluation of the Efficacy of an Ankle-Foot Cast on Walking Recovery Early After Stroke: SWIFT Cast Trial. (January 2016) - Pomeroy, Valerie M.; Rowe, Philip; Clark, Allan; Walker, Andrew; Kerr, Andrew; Chandler, Elizabeth; Barber, Mark; Baron, Jean-Claude; ,
Background . Timely provision of an ankle-foot orthosis (AFO) orthotist customized for individuals early after stroke can be problematic. Objective . To evaluate the efficacy of a therapist-made AFO (SWIFT Cast) for walking recovery. Methods . This was a randomized controlled, observer-blind trial. Participants (n = 105) were recruited 3 to 42 days poststroke. All received conventional physical therapy (CPT) that included use of "off-the-shelf" and orthotist-made AFOs. People allocated to the experimental group also received a SWIFT Cast for up to 6 weeks. Measures were undertaken before randomization, 6 weeks thereafter (outcome), and at 6 months after stroke (follow-up). The primary measure was walking speed. Clinical efficacy evaluation used analysis of covariance. Results . Use of a SWIFT Cast during CPT sessions was significantly higher ( P < .001) for the SWIFT Cast (55%) than the CPT group (3%). The CPT group used an AFO in 26% of CPT sessions, compared with 11% for the SWIFT Cast group ( P = .005). At outcome, walking speed was 0.42 (standard deviation [SD] = 0.37) m/s for the CPT group and 0.32 (SD = 0.34) m/s for the SWIFT Cast group. Follow-up walking speed was 0.53 (SD = 0.38) m/s for the CPT group and 0.43 (0.34) m/s for the SWIFT Cast group. Differences, after accounting for minimization factors, were insignificant at outcome ( P = .345) and follow-up ( P = .360). Conclusion and implications . SWIFT Cast did not enhance the benefit of CPT, but the control group had greater use of another AFO. However, SWIFT Cast remains a clinical option because it is low cost and custom-made by therapists who can readily adapt it during the rehabilitation period.